2011
DOI: 10.1371/journal.pone.0019840
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Development of an In Vivo BCG Challenge Model for Testing Candidate TB Vaccine Efficacy

Abstract: There is an urgent need for an immunological correlate of protection against tuberculosis (TB) with which to evaluate candidate TB vaccines in clinical trials. Development of a human challenge model of Mycobacterium tuberculosis (M.tb) could facilitate the detection of such correlate(s). Here we propose a novel in vivo Bacille Calmette-Guérin (BCG) challenge model using BCG immunization as a surrogate for M.tb infection. Culture and quantitative PCR methods have been developed to quantify BCG in the skin, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 41 publications
6
44
0
1
Order By: Relevance
“…The question of BCG persistence has been noted in previous studies in mice [24,25,27,[32][33][34][35], other animal models [23,26] and humans [36,37]. In a similar study using C57BL/6 mice and M. tb challenge [27], spleen protection was reduced by 75%, but in contrast lung immunity was unaffected.…”
Section: Discussionmentioning
confidence: 80%
“…The question of BCG persistence has been noted in previous studies in mice [24,25,27,[32][33][34][35], other animal models [23,26] and humans [36,37]. In a similar study using C57BL/6 mice and M. tb challenge [27], spleen protection was reduced by 75%, but in contrast lung immunity was unaffected.…”
Section: Discussionmentioning
confidence: 80%
“…We believe that in the absence of molecular signatures for the dynamic states of the infection that enable prediction of the course of disease and effects of interventions on correlates of protection, it may be necessary to think about developing a safe live infection challenge model that could be used in small-scale studies to measure ability to kill the pathogen (186). This has been a very important tool in studying protection in other infectious diseases, such as malaria and cholera.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies (20)(21)(22) suggest that the main differences in BCG vaccination in different animal models are due to the substrain of BCG utilized, which leads to different qualitative and quantitative immune responses while resulting in similar reductions in the bacterial burden after challenge with an M. tuberculosis strain. Our study contradicts previous reports by Kramnik's laboratory which demonstrated similar adaptive T cell responses between congenic murine strains differing in the sst locus (15).…”
Section: Discussionmentioning
confidence: 99%